Trauma-induced Exacerbation of Chronic Inflammatory Back Pain in a Case of Aggravated Sacroiliitis - Anoovab Saha; Raktim Swarnakar; Pankaj Kumar Mandal; Soumyadipta Ghosh (Indian Journal of Physical Medicine & Rehabilitation)
Ankylosing spondylitis (AS) is a leading cause of chronic inflammatory low back pain (LBP). A 30-year-old male presented with worsening LBP and difficulty in walking over the last 18 months. Initially, 5 years back, he was diagnosed with AS when he started to experience LBP with morning stiffness (>2 h) and lethargy. Symptoms were then manageable with medications. For 2 years, it was mild. After that, 3 years back, he met with a road traffic accident causing a sacral fracture and bilateral pubic rami fractures. Even after trauma, his symptoms were stable for 18 months (post-trauma phase) but then (last 18 months from now) worsened, with severe LBP and intense morning stiffness. Imaging studies and elevated C-reactive protein levels indicated aggravated inflammation. This case highlights the role of trauma in accelerating AS progression and emphasises the need to investigate post-traumatic joint pain to identify potential underlying inflammatory conditions like AS.